Surveying the ethical dimensions of international security from the perspective of Ayatollah Javadi Amoli - Najaf Lakzaei (اخلاق وحیانی)
The main question of this research is that what the Islamic moral tools are for providing international security? In other words, how can stop the war and bring peace and security to the people of the world? In the current situation we need to explain the importance of this question, because human security in the world today suffers from degeneration. The writer in this research has tried, by inferential method, to answer this question according to Ayatollah Javadi Amoli's works. The author of this article claims that the islamic tools for providing international security are available in several dimentions. One is the levels of analysis that are  three: Islamic world, monotheistic religions, and all the world. Second, the amount of inclusion that is divided in two groups; shared by all three levels and specific of each level. This article deals with both issues. Conceptual and theoretical foundation of discussions in this research is the theory of natural savagery and natural civilization of human. The characteristics of Islam make us to claim that the only source and basis for providing international security is Islmic teachings, especially its moral teachings.